Testing static tradeoff against pecking order models of capital structure: a critical comment - Chirinko, Robert S; Singha, Anuja R (Journal of Financial Economics, 2000)
In a recent paper, Shyam-Sunder and Myers (1999) introduce a new test of the Pecking Order Model. This comment shows that their elegantly simple test generates misleading inferences when evaluating plausible patterns of external financing. Our results, coupled with the power problem with the Static Tradeoff Model documented by Shyam-Sunder and Myers, indicate that their empirical evidence can evaluate neither the Pecking Order nor Static Tradeoff Models. Alternative tests are needed that can identify the determinants of capital structure and can discriminate among competing hypotheses.